Interference and economic damage level of alexandergrass in beans as a function of plant density - Galon, Leandro (2022)
The study of bean sowing density and the level of economic damage (EDL) caused by alexandergrass (Urochloa plantaginea) are important tools for adequately adopting the integrated management of this weed and, thus, producing food with higher quality and less pesticide residue. Therefore, the objective of this work was to evaluate the interference and the level of the economic damage of alexandergrass in competition with the common bean, estimated as a function of sowing densities of the crop and the weed. The bean cultivar IPR Uirapuru was used. The treatments consisted of four bean densities (140,000; 180,000; 220,000 and 260,000 plants ha-1, respectively) and alexandergrass that varied from 0 to the maximum of 104 plants m-2. The experiment was installed in a Red Aluminoferric Latosol, at the experimental area of the Federal University of the Southern Border, campus Erechim/RS, on 10/31/2016. We used the rectangular hyperbola model to describe the relationship between the loss of bean grain yield and the explanatory variables of plant density (DP), soil cover (CS), leaf area (AF) and shoot dry matter (MS). Therefore, the variables CS and DP can be used instead of AF and MS to estimate grain yield losses in common beans. The density of 260,000 plants ha-1 of bean showed greater competitiveness with alexandergrass and the highest values of EDLs, justifying the adoption of weed control management at higher densities.